Strategic Business Diversification and Competitive Positioning in Railway Infrastructure Maintenance - Akhmad Yani Qorry; Arif Imam Suroso; Asep Taryana (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The growth of the national railway industry, the expansion of rail networks, and the increasing safety standards have driven the need for more modern, integrated, and sustainable railway infrastructure maintenance services. These conditions create opportunities to diversify into the railway infrastructure maintenance business. This study aims to formulate appropriate strategies for the company to enter the industry competitively. The research uses a descriptive qualitative approach supported by quantitative analysis. This research integrates the PESTLE framework, Porter’s five forces, VRIO, SWOT–TOWS, and the quantitative strategic planning matrix. Data were collected through expert interviews, questionnaires, and document analysis. The results show that the track maintenance industry has high entry barriers, significant dependence on OEMs, strong buyer power, and complex technological and certification requirements. However, opportunities emerge through long-term Public-Private Partnership (PPP) contracts, urban/HSR projects, maintenance digitalization, and technical specialization in track and slab-track segments. The priority strategies derived include forming OEM alliances, strengthening equipment capacity, establishing an internal certification academy, and adopting predictive maintenance to improve tender scores and SLA performance. These findings provide strategic direction to expand its portfolio and strengthen competitiveness in the railway maintenance sector.